CRITICAL STUDY OF THE CONTRIBUTION OF MARKFED IN AGRICULTURAL STABILITY OF CHHATTISGARH STATE (WITH SPECIAL REFERENCE TO BILASPUR DIVISION) - Sharma, Manya; Bhave, Sampada (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Indian economy is an agriculture based economy. 50% of the population of India still depends on agriculture activities for their livelihood and survival. Agriculture has an important place in the economy as it provides employment to about 54.5% of the population and is also a means of earning valuable foreign exchange. Therefore, the prosperity and development of the state lies in the increase in agricultural productivity. Markfed has been established by the Chhattisgarh government for the overall development of agriculture. Through this research paper, an attempt has been made to analyze the contribution of Markfed to the stability and potential profit in the agricultural sector in Chhattisgarh.